RESILIENSI HUBUNGAN INDUSTRIAL PANCASILA: MENAKAR EFEKTIVITAS ADVOKASI KOLEKTIF TERHADAP TRANSFORMASI STATUS KERJA PASCA PUTUSAN MAHKAMAH KONSTITUSI - Ruby W H Oktolina Samosir; Anak Agung Dewi Intan Parwati; Robert L Simanungkalit (Pojok Publisher, 2025)
Pancasila Industrial Relations (HIP) is the foundation of Indonesian employment, prioritizing deliberation and consensus. However, its implementation faces significant challenges with the normalization of the outsourcing system and flexible work practices in the Job Creation Law. This paper analyzes the resilience of HIP through the advocacy movement of labor unions in responding to uncertainty about employment status. Using a juridical-normative approach, this paper examines how the Constitutional Court's ruling on the judicial review of the Job Creation Law has become a new instrument for labor unions to fight for legal certainty. The results show that collective advocacy remains a key bulwark in maintaining the balance between company productivity and workers' normative rights amidst the current liberalization of the labor market.